Radiative recombination model for BiSeI microcrystals: unveiling deep defects through photoluminescence - Marc Dolcet Sadurni; Jüri Krustok; Kristi Timmo; Valdek Mikli; Rokas Kondrotas; Maarja Grossberg-Kuusk; Marit Kauk-Kuusik (JPhys Energy)
Pnictogen chalcohalides are semiconductors that have emerged as promising materials for energy conversion due to their exceptional optoelectronic properties. Their electronic configuration (ns ^2 ), particularly for Bi- and Sb-based compounds, can be a key factor in efficient carrier transport and defect tolerance, similarly, to Pb-perovskites. In the present study, the Bi-containing chalcohalide, bismuth selenoiodide (BiSeI) was synthesized via isothermal heat treatment of binary precursors in evacuated quartz ampoules. The synthesized BiSeI microcrystals exhibited a characteristic needle-like morphology and a near-stoichiometric composition. Both indirect and direct band gap energies of BiSeI were determined by ultraviolet–visible–near-infrared diffuse reflectance spectroscopy, with room temperature values of 1.17 eV and 1.29 eV, respectively. This study presents the first experimental investigation of the photoluminescence properties of BiSeI microcrystals resulting in a recombination model involving multiple defect states. This work provides valuable insights into the defect structure and recombination mechanisms within BiSeI, paving the way for further exploration of its potential in optoelectronic devices.